Exploring the Impact of Teacher Commitment and School Culture on Performance Outcomes in Elementary Education - Isnawati Isnawati; Suarman Suarman; Sumarno Sumarno; Ijayani Ijayani (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study examines the impact of teacher commitment and school culture on teacher performance in the State Elementary Schools of Pinggir District, Bengkalis Regency. Employing a quantitative methodology and an ex post facto research design, the study involves a population of 358 elementary school teachers. A sample of 66 teachers was selected using the Slovin formula with a 10% error margin, and an additional 20 teachers participated in a preliminary trial. Data were collected via questionnaires administered through Google Forms. Analysis was conducted using inferential statistics in SPSS (Statistical Package for the Social Sciences) Version 23, incorporating classical assumption tests—normality and linearity tests—as well as hypothesis testing through F tests, correlation tests, and determinant tests. The findings reveal that both teacher commitment and school culture significantly influence teacher performance individually and collectively. Enhanced commitment and positive school culture correlate with improved educational delivery, which in turn boosts student achievement and overall school performance.